Bernardim Ribeiro, Menina e Moça ou Saudades, edição de Juan M. Carrasco González, Coimbra, Angelus Novus, 2008 - Araújo, Teresa (Limite. Revista de estudios portugueses y de la lusofonía, 2022)
recensión